On the quasi-ordinary cuspidal foliations in ( C3, 0 ) - Fernández-Sánchez P. (2006)
Both authors partially supported by CONCYTEC (Peru) under the research project 551-OAJ (2004), and by Junta de Castilla y León (Spain) under project VA123/04.